Leadership Style, Work Environment, and Compensation on Job Satisfaction and Teacher Performance - Sriadmitum, Ike; Sudarno; Nyoto (Journal of Applied Business and Technology, 2023)
This study aims to analyze the effect of leadership style, work environment, and compensation on job satisfaction and performance of state high school teachers in Tandun and Ujung Batu sub-districts. This research is quantitative research by distributing questionnaires to respondents. The population in this study were all public high school civil servant teachers in Tandun and Ujung Batu sub-districts. The sample selection technique uses the census method. The sample in this study amounted to 90 respondents. The data analysis technique used Structural Equation Modeling (SEM) PLS. The results of this study indicate that leadership style has no significant effect on job satisfaction, leadership style has no significant effect on teacher performance, positive and significant work environment on job satisfaction, the work environment has no significant effect on performance, compensation has no significant effect on job satisfaction, compensation does not significant effect on teacher performance, teacher performance has no significant effect on job satisfaction.